The reductions of oxalate and its precursors in cloud droplets relative to wet particles. (15th August 2020) - Lin, Qinhao; Yang, Yuxiang; Fu, Yuzhen; Jiang, Feng; Zhang, Guohua; Peng, Long; Lian, Xiufeng; Bi, Xinhui; Li, Lei; Chen, Duohong; Ou, Jie; Tang, Mingjin; et al.
Abstract: The formation mechanism of oxalate in the aqueous phase remains uncertain. Approximately 600 000 oxalate-containing particles and 450 000 its precursors-containing particles (e.g., acetate, glyoxylate, pyruvate and malonate) were obtained using a single particle aerosol mass spectrometer at a mountain site in southern China from 9 May to 4 June, 2018. The number fraction of oxalate or its precursors was compared within three representative aerosols with different liquid water contents including cloud droplet residues (RES), cloud interstitial particles (INTER) and cloud-free ambient particles (AMB). Lower number fraction of oxalate was found in the RES relative to INTER and AMB, mostly attributed to the decrease in precursors. This was conflicted with the enhancement of in-cloud oxalate formation previously reported. Further analysis indicated that the aerosol acidity had a major influence on the formation of precursors and their conversion to oxalate. With the increase of relative aerosol acidity (defined as the sum of sulfate and nitrate peak areas divided by ammonium peak area), the formation of precursors was increased while the conversion of precursors to oxalate was suppressed. Meanwhile, this influence was more pronounced in the INTER and AMB relative to RES. This work highlighted the roles of aerosol acidity and liquid water content in the aqueous phase formations of oxalate and its precursors. Highlights: Reduction of oxalate was found in cloud droplets residues relative to wet particles. Enhanced relative aerosol acidity increased the formation of oxalate precursors. Enhanced relative aerosol acidity suppressed the conversion of precursors to oxalate.